When the dead rise - narratives of the Revenant, from the Middle Ages to the present day - LIVERMORE, CHRISTIAN ([S.l.] : D S BREWER, 2021)
A survey of the motif of the revenant, showing how medieval themes and motifs persist today.
1. The Corpse in Christianity: The Dead, Mostly Dead and Very Special Dead -- 2. The Religious Revenant -- 3. The Corpse as Admonition, Art and Bogeyman -- 4. The Reformed Revenant -- 5. The Dead Rise -- in Literature.
Includes bibliographical references and index.
JSTOR
Keywords: Death -- Folklore; Eschatology; Mort -- Folklore; Death; Eschatology; Folklore